Penerapan Algoritma Evolutionary dan Nearest Neighbor untuk Optimasi Rute Distribusi - Utami, Rika Sri; Arifin, Riski; Lufika, Raihan Dara; Dio, Rafi; Manihuruk, Hendrik Vicarlo Saragih (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2024)
The distribution route is a common issue faced by companies. Companies need to distribute goods to optimize delivery and operational shipping costs. Company XYZ distributes goods to 9 retailers. The problem encountered is that delivery relies only on the intuition of the delivery operators, which is considered suboptimal. Therefore, finding the shortest distribution distance is necessary, one of which can be done using an evolutionary algorithm. An evolutionary algorithm is a population-based stochastic search used to find optimal solutions to a problem. Additionally, distributing goods using the nearest neighbor method determines the route based on the shortest distance between retailers. Thus, the purpose of this study is to find the shortest distribution distance for goods delivered to 9 retailers using an evolutionary algorithm and the nearest neighbor method. The results show that using the evolutionary algorithm, the minimum total distance is 54.5 kilometers, with the route being warehouse-2-1-5-9-4-6-7-3-8-warehouse, while using the nearest neighbor method yields a distance of 55 kilometers, resulting in a difference of 0.5 kilometers.